Understanding social responsibility's influence on service quality and student satisfaction in higher education - Santos, G.; Marques, C. S.; Justino, E.; Mendes, L. (Journal of Cleaner Production, 2020)
Understanding customers’ expectations regarding organisations’ social responsibility is fundamental to creating and implementing successful strategies and programmes. More specifically, this process requires the development of a theoretical framework in order to analyse the impact of universities’ social responsibility strategies on service quality and students’ satisfaction with higher education. The present study sought to identify the factors defining students’ perceptions of university social responsibility (USR) and to analyse its impact on their satisfaction and service quality. The research was carried out in a Portuguese higher education institution, with a sample of 903 students. Structural equation modelling was used to test the proposed research model. The results validate this explanatory model of USR and the latter's influence on service quality and higher education students’ satisfaction. Concerning USR's effects, the findings include that, from the students’ perspective, USR contributes most directly to quality education through USR's cognitive impacts, that is, those associated with research. This study's results also corroborate that a strategy focused on sustainable development (i.e. promoting a responsible university) influences students’ positive perceptions and functions as an antecedent of service quality and student satisfaction.